STRATEGI PEMASARAN REKSADANA PADA PT. ASSET MANAJEMEN SINARMAS CABANG PADANG - Mukti Diapepin; Naufal Raid; Syaidil Hakimi (Jurnal Public Administration, Business and Rural Development Planning, 2022)
Based on the limitation of the problem above, the writer formulates the problem in this research as follows: 1) How is the Mutual Fund Marketing Strategy at PT. Sinarmas Padang Branch Asset Management. 2) What are the obstacles faced in relation to the Mutual Fund Marketing Strategy at PT. Sinarmas Padang Branch Asset Management. 3) How are the efforts made in overcoming the obstacles faced in connection with the Mutual Fund Marketing Strategy at PT. Asset Management Sinarmas Padang Branch The purpose of the research that the author did were: 1) To find out how the Mutual Fund Marketing Strategy at PT. Sinarmas Padang Branch Asset Management. 2) To find out how the obstacles faced in relation to the Mutual Fund Marketing Strategy at PT. Sinarmas Padang Branch Asset Management. 3) To find out how the efforts made in overcoming the obstacles faced in relation to the Mutual Fund Marketing Strategy at PT. Asset Management Sinarmas Padang Branch The research method used is a descriptive method with a qualitative approach. Mutual Fund Marketing Strategy Problems Handling Customer Complaints at Branch Offices many officers are carried out by these employees causing the employee focus to be divided between doing Marketing (Marketing) and Handling Customer Complaints, so that based on information received by employees, employees feel that they are not optimal in conducting Mutual Sales fund Conclusions are as follows: 1) Marketing Strategy to Increase Sales of Mutual Funds at PT. Asset Management Sinarmas Padang Branch The increasingly rapid progress of Mutual Fund sales activities has led to intense business competition. Likewise for PT. Asset Management Sinarmas Padang Branch which sells similar goods. With the similar products sold by PT. Sinarmas Padang Branch Asset Management is different, while consumer desires are diverse, making consumers free to choose products that can satisfy their needs. 2) The problems found in the Marketing Strategy of PT Asset Management Sinarmas Padang Branch. The number of competitors from other banks and less familiar among the general public. 3) Efforts were made to overcome these problems, introduced an investment product called Mutual Funds to Boost the Spirit of Marketing Performance Where Mutual Funds are a forum used to collect funds from the investor community to be reinvested in securities portfolios by investment managers